Compassionate Use of Remdesivir in Pregnant Women With Severe Coronavirus Disease 2019. (8th October 2020) - Burwick, Richard M; Yawetz, Sigal; Stephenson, Kathryn E; Collier, Ai-Ris Y; Sen, Pritha; Blackburn, Brian G; Kojic, E Milunka; Hirshberg, Adi; Suarez, Jose F; Sobieszczyk, Magdalena E; Marks, Kristen M; Mazur, Shawn; et al.
Abstract: Background: Remdesivir is efficacious for severe coronavirus disease 2019 (COVID-19) in adults, but data in pregnant women are limited. We describe outcomes in the first 86 pregnant women with severe COVID-19 who were treated with remdesivir. Methods: The reported data span 21 March to 16 June 2020 for hospitalized pregnant women with polymerase chain reaction–confirmed severe acute respiratory syndrome coronavirus 2 infection and room air oxygen saturation ≤94% whose clinicians requested remdesivir through the compassionate use program. The intended remdesivir treatment course was 10 days (200 mg on day 1, followed by 100 mg for days 2–10, given intravenously). Results: Nineteen of 86 women delivered before their first dose and were reclassified as immediate "postpartum" (median postpartum day 1 [range, 0–3]). At baseline, 40% of pregnant women (median gestational age, 28 weeks) required invasive ventilation, in contrast to 95% of postpartum women (median gestational age at delivery 30 weeks). By day 28 of follow-up, the level of oxygen requirement decreased in 96% and 89% of pregnant and postpartum women, respectively. Among pregnant women, 93% of those on mechanical ventilation were extubated, 93% recovered, and 90% were discharged. Among postpartum women, 89% were extubated, 89% recovered, and 84% were discharged. Remdesivir was well tolerated, with a low incidence of serious adverse events (AEs) (16%). Most AEs were related to pregnancy and underlying disease; most laboratory abnormalities were grade 1 or 2. There was 1 maternal death attributed to underlying disease and no neonatal deaths. Conclusions: Among 86 pregnant and postpartum women with severe COVID-19 who received compassionate-use remdesivir, recovery rates were high, with a low rate of serious AEs. Abstract : Among 86 pregnant and postpartum women with severe coronavirus disease 2019 who received compassionate-use remdesivir, recovery rates from serious infection were high with a low rate of serious adverse events.